Oral wound material and method of making same

CN117942431BActive Publication Date: 2026-10-20蔓华(山东)医学科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410101012.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-24
Publication Date
2026-10-20
Estimated Expiration
2044-01-24

AI Technical Summary

Technical Problem

[0006]有鉴于此,本申请的目的在于提供一种口腔创口材料及其制备方法,以解决现有技术中存在的口腔创口材料体积维持性差、力学强度低、降解速度快,孔结构不均匀、难以与患者伤处充分匹配等问题

Benefits of technology

[0026](1)本申请中的口腔创口材料通过胶原悬液冻干获得,胶原悬液由凝胶状胶原液和胶原纤维液获得,凝胶状胶原液和胶原纤维液由脱细胞基质进一步加工获得。其中,凝胶状胶原液是通过对酸溶胀的脱细胞基质充分粉碎而制成的一种粘弹性的凝胶态体系,体系均一且存在更多的物理缠结,冻干后可以获得孔结构比较均一的结构,但是由于破坏了大部分纤维间的天然连接,使得其力学强度低,易降解;胶原纤维液制备过程中使用的脱细胞基质颗粒较大,保持了更多的天然结构,力学强度高,降解时间较长。但是胶原纤维液是一个不稳定的分散体系,当把胶原纤维液单独制备成冻干海绵后,海绵结构不均匀,且吸水后容易溃散,这是因为胶原纤维间的作用强度低所致。因此,我们将凝胶状胶原液和胶原纤维液按照一定比例混合,其中凝胶状胶原液也起到了一种增稠剂或粘结剂的作用,增强胶原纤维间的相互作用,使最终得到的口腔创口材料兼具力学性能和均匀孔结构的性能,体积稳定性好,吸液后不容易发生溃散现象。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117942431B_ABST
    Figure CN117942431B_ABST
Patent Text Reader

Abstract

The application relates to an oral wound material and a preparation method thereof, wherein the preparation method of the oral wound material comprises the following steps: S1, preparing a gelatinous collagen liquid; S2, preparing a collagen fiber liquid; S3, mixing 5-30 parts of the gelatinous collagen liquid and 70-95 parts of the collagen fiber liquid, uniformly stirring and vacuum defoaming to obtain a collagen suspension; S4, extruding and injecting the collagen suspension into a mold to be shaped and freeze-dried to obtain a collagen freeze-dried sponge; and S5, physically crosslinking the collagen freeze-dried sponge to obtain the oral wound material. The oral wound material prepared by the above method has the advantages of high mechanical strength, good volume maintenance and long degradation time, can better maintain the stability of blood clots at tissue defect sites, and promotes tissue regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of biomaterials technology, and in particular to an oral wound material and its preparation method. Background Technology

[0002] Tooth extraction is a common treatment procedure performed by oral and maxillofacial surgeons and general dentists. Dental diseases are prevalent in the general population, necessitating tooth extraction. Post-extraction infection due to bleeding, mucosal damage, and foreign bodies entering the wound is a common occurrence, with dry socket being the most frequent complication, potentially caused by various systemic or local factors. Packing is a common method for managing bleeding from the extraction socket and protecting the wound surface. Appropriate selection of wound materials for local filling of the extraction socket is an effective measure to prevent and treat post-extraction bleeding and infection caused by foreign bodies.

[0003] Collagen sponge is the most widely used filling material after tooth extraction on the market. It can stop bleeding, prevent foreign bodies from entering, and protect the wound, making it a relatively ideal filling material. Currently, most collagen sponges are made from collagen extracted from bovine Achilles tendons, resulting in a loose sponge structure with uniform pores. However, during the extraction process from bovine Achilles tendons, the natural cross-linking structure between collagen fibers is completely destroyed, leading to the following problems with collagen sponges: 1. Poor volume retention and low strength; after absorbing blood, they struggle to maintain their original shape, easily collapsing and providing poor support, thus affecting the bone formation of the extraction socket; 2. Rapid degradation; it degrades quickly in vivo, within 1-2 weeks. This degradation rate is mismatched with the tissue regeneration rate, and excessively rapid degradation can affect the preservation of the extraction site. These problems limit the application of collagen sponge products in clinical dentistry.

[0004] Decellularized matrix retains most of its natural cross-linked structure, exhibiting advantages such as high mechanical strength and long degradation time. Further processing of the decellularized matrix to create a sponge structure effectively avoids the drawbacks of collagen sponges extracted from bovine Achilles tendons. Chinese invention patent (application number CN202211625002.0) discloses a decellularized matrix wound material and its preparation method. The product is shaped like a cannonball or a frustum, made from decellularized matrix. The upper part has high density, high support strength, and small pore size, effectively preventing foreign body entry; the lower part has low density, large pore size, and good liquid absorption, accelerating hemostasis and rapidly forming blood clots, promoting wound healing and bone tissue repair. It is obtained by pulverizing the decellularized matrix into ultrafine powder, followed by centrifugation, freeze-drying, and cross-linking to obtain a porous structure. Because the decellularized matrix ultrafine powder is essentially composed of relatively independent decellularized matrix particles, the lack of interparticle bonding strength results in an uneven pore structure and mechanical strength in the final sponge-like wound material, poor volume retention, and easy disintegration after liquid absorption.

[0005] Therefore, there is an urgent need to develop an oral wound material with good volume retention, long degradation time, and uniform pore structure that can stabilize blood clots in extraction sockets and promote the formation of new bone within the extraction socket. Summary of the Invention

[0006] In view of this, the purpose of this application is to provide an oral wound material and its preparation method, so as to solve the problems of poor volume maintenance, low mechanical strength, fast degradation rate, uneven pore structure, and difficulty in fully matching the patient's wound in the prior art.

[0007] This invention provides a method for preparing oral wound material, comprising:

[0008] S1: Prepare gel-like collagen solution;

[0009] S2: Preparation of collagen fiber solution;

[0010] S3: Mix 5-30 parts of gel-like collagen solution and 70-95 parts of collagen fiber solution, stir evenly and remove bubbles under vacuum to obtain collagen suspension;

[0011] S4: The collagen suspension is squeezed into a mold to form a shape and then freeze-dried to obtain a collagen freeze-dried sponge;

[0012] S5: Physically cross-link the freeze-dried collagen sponge to obtain oral wound material.

[0013] Furthermore, the preparation steps of the gel-like collagen solution include:

[0014] S101 Decellularization: A decellularized matrix is ​​prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;

[0015] S102 pulverization: After the decellularized matrix is ​​shredded, it is suspended in pure water to make the mass percentage of the decellularized matrix 0.5%-3.0%. The pH is adjusted to 3.0-4.0 with acid. The decellularized matrix is ​​pulverized into a gel state using a tissue homogenizer to obtain a gel-like collagen solution.

[0016] Furthermore, the preparation step of the collagen fiber solution includes:

[0017] S201 Decellularization: A decellularized matrix is ​​prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;

[0018] S202 pulverization: The decellularized matrix is ​​pulverized into irregular particles with a particle size of 0.2mm-2mm by low-temperature grinding and suspended in water, so that the mass percentage of the decellularized matrix particles is 0.5%-3.0%. The pH value is adjusted to 2.5-3.0 with acid to allow the decellularized matrix particles to fully swell, thus obtaining a decellularized matrix suspension.

[0019] S203 Dehydration: Add sodium chloride powder to the decellularized matrix mixture until the sodium chloride concentration reaches 2.0-2.5 mol / L to obtain a white salting-out precipitate; wash the white salting-out precipitate with PBS buffer and centrifuge to obtain concentrated collagen fibers;

[0020] S204 dispersion: Collagen fibers are placed in an acid with a pH of 3.0-4.0, so that the mass percentage of collagen fibers is 1%-6%. The collagen fibers are then mechanically stirred to form a slightly swollen and uniformly dispersed state, resulting in a collagen fiber solution.

[0021] Furthermore, the acid includes hydrochloric acid, acetic acid, and citric acid.

[0022] Furthermore, the naturally derived tissues include the submucosa of the small intestine of pigs or cattle, the peritoneum of pigs or cattle, the pericardium of pigs or cattle, the dermis of pigs or cattle, and the bladder of pigs or cattle.

[0023] Furthermore, the physical crosslinking is a gradient thermal crosslinking process, in which the collagen freeze-dried sponge is placed in a vacuum chamber, evacuated to less than -100 kPa, and kept at 25℃-30℃ for 1-2 hours; then the temperature is gradually increased for crosslinking, from 80℃-85℃ for 2-3 hours; then the temperature is further increased to 100℃-105℃ for 2-3 hours; and finally the temperature is increased to 120℃-125℃ for 24-48 hours.

[0024] This application also provides an oral wound material, prepared by the above-described method for preparing oral wound materials, comprising a gel-like collagen liquid freeze-dried layer and a collagen fiber liquid freeze-dried layer interwoven with each other, which may be in sheet or cylindrical form.

[0025] The beneficial effects of this invention are:

[0026] (1) The oral wound material in this application is obtained by freeze-drying a collagen suspension. The collagen suspension is obtained from gel-like collagen solution and collagen fiber solution, which are further processed from decellularized matrix. The gel-like collagen solution is a viscoelastic gel system prepared by thoroughly pulverizing an acid-swollen decellularized matrix. The system is homogeneous and contains more physical entanglements. After freeze-drying, it can obtain a relatively uniform pore structure. However, due to the destruction of most of the natural connections between fibers, its mechanical strength is low and it is easily degraded. The decellularized matrix particles used in the preparation of the collagen fiber solution are larger, retain more of the natural structure, have high mechanical strength, and a longer degradation time. However, the collagen fiber solution is an unstable dispersion system. When the collagen fiber solution is prepared into a freeze-dried sponge, the sponge structure is uneven and it easily collapses after absorbing water. This is due to the low interaction strength between collagen fibers. Therefore, we mix gel-like collagen solution and collagen fiber solution in a certain proportion. The gel-like collagen solution also acts as a thickener or binder, enhancing the interaction between collagen fibers. This results in a final oral wound material that combines mechanical properties with a uniform pore structure, exhibits good volume stability, and is less prone to disintegration after liquid absorption.

[0027] (2) The oral wound material in this application is obtained after physical cross-linking treatment. Physical cross-linking increases the interaction between collagen fibers, making the oral wound material more volume-maintaining and ensuring good biocompatibility. The oral wound material of this invention, after reasonable design and processing, overcomes the shortcomings of poor volume maintenance and mechanical properties and rapid degradation in the prior art. The oral wound material enhanced by physical entanglement and physical cross-linking also has stable mechanical properties and volume maintenance after absorbing water, and there is no visible collapse after applying pressure. Attached Figure Description

[0028] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0029] Figure 1 This is a scanning electron microscope image of the surface of the oral wound material prepared in Example 1;

[0030] Figure 2 This is a comparison chart of three samples under different conditions. Detailed Implementation

[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] This invention provides a method for preparing oral wound material, comprising the following steps:

[0033] S1: Prepare gel-like collagen solution;

[0034] S2: Preparation of collagen fiber solution;

[0035] S3: Mix 5-30 parts of gel-like collagen solution and 70-95 parts of collagen fiber solution, stir evenly and remove bubbles under vacuum to obtain collagen suspension;

[0036] S4: The collagen suspension is squeezed into a mold to form a shape and then freeze-dried to obtain a collagen freeze-dried sponge;

[0037] S5: Physically cross-link the freeze-dried collagen sponge to obtain oral wound material.

[0038] The oral wound material obtained by the above method is prepared by freeze-drying collagen suspension. It has good volume retention, high mechanical strength, and a uniform pore structure. It can quickly absorb blood and body fluids, stabilize blood clots, and maintain the space required for bone tissue regeneration.

[0039] The collagen suspension in this invention is prepared from gel-like collagen solution and collagen fiber solution. Both the gel-like collagen solution and the collagen fiber solution are prepared from decellularized matrix of animal tissues of natural origin. The animal tissues of natural origin can be one of the following: submucosa of pig or bovine small intestine, peritoneum of pig or bovine, pericardium of pig or bovine, dermis of pig or bovine, or bladder of pig or bovine.

[0040] Specifically, the preparation steps of the gel-like collagen solution include:

[0041] S101 Decellularization: A decellularized matrix is ​​prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;

[0042] S102 pulverization: The decellularized matrix after decellularization treatment is cut into small pieces and suspended in pure water. The mass percentage of the decellularized matrix is ​​0.5%-3.0%. The pH value of the pure water is adjusted to 3.0-4.0 with acid. The decellularized matrix is ​​pulverized into a gel state using a tissue homogenizer to obtain a gel-like collagen solution.

[0043] In some preferred embodiments, since the decellularized matrix can swell in an acidic solution, and with the strong shearing and mixing effect of the tissue homogenizer, the decellularized matrix is ​​pulverized into ultrafine fibers and further swells, causing the solution viscosity to gradually increase, and finally a viscous gel-like collagen solution is obtained.

[0044] In some preferred embodiments, the acid may be one of hydrochloric acid, acetic acid, and citric acid.

[0045] In some preferred embodiments, the mass percentage of decellularized matrix in pure water is preferably 0.5%-3.0%. This is because when the mass percentage of decellularized matrix is ​​less than 0.5%, the final collagen solution is a fluid solution with low viscosity, which will have an adverse effect on the subsequent preparation process of collagen suspension. When the mass percentage of decellularized matrix is ​​greater than 3.0%, the final collagen solution will lose its fluidity due to excessive concentration, resulting in some swollen particles not being fully pulverized, thus affecting the pulverization effect.

[0046] In some preferred embodiments, since the viscosity of the final obtained gel-like collagen solution is related to the pH value, the lower the pH value within a certain range, the greater the viscosity. In order to avoid the gel-like collagen solution having too high a viscosity and affecting the pulverization effect, the pH value of the pure water with the decellularized matrix suspended is preferably adjusted to 3.0-4.0 by acid.

[0047] In some preferred embodiments, the preparation steps of the collagen fiber solution are as follows:

[0048] S201 Decellularization: A decellularized matrix is ​​prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin;

[0049] S202 pulverization: The decellularized matrix is ​​pulverized into irregular particles with a particle size of 0.2mm-2mm by low-temperature grinding and suspended in pure water. The mass percentage of the decellularized matrix particles is 0.5%-3.0%. Then, the pH value of the pure water is adjusted to 2.5-3.0 with acid to fully swell the decellularized matrix particles and obtain a decellularized matrix suspension.

[0050] S203 dehydration: Add sodium chloride powder to the decellularized matrix suspension until the sodium chloride concentration reaches 2.0-2.5 mol / L to obtain a white salting-out precipitate. Wash the white salting-out precipitate with PBS buffer and centrifuge to obtain concentrated collagen fibers.

[0051] S204 dispersion: Collagen fibers are placed in an acid with a pH of 3.0-4.0, so that the mass percentage of collagen fibers is 1%-6%. The collagen fibers are then mechanically stirred to form a slightly swollen and uniformly dispersed state, thus obtaining a collagen fiber solution.

[0052] In some preferred embodiments, the acid may be one of hydrochloric acid, acetic acid, and citric acid.

[0053] In some preferred embodiments, during the preparation of collagen fiber solution, the pulverized decellularized matrix particles swell in an acid with a pH of 2.5-3.0, and are then dehydrated by salting out to obtain loose white collagen fibers. In order to maintain the natural structure of the decellularized matrix to a certain extent, the particle size of the pulverized decellularized matrix is ​​preferably 0.2 mm-2 mm.

[0054] In some preferred embodiments, to avoid separation of collagen fiber liquid, the collagen fibers are dispersed in an acid with a pH of 3.0-4.0 to allow the collagen fibers to swell slightly, and then uniformly dispersed by mechanical stirring.

[0055] In some preferred embodiments, in order to match the collagen fiber solution with the gel-like collagen solution, the pH value of the collagen fiber solution should be the same as that of the gel-like collagen solution.

[0056] After the gel-like collagen solution and collagen fiber solution are prepared separately, they are mixed in proportion, stirred evenly, and defoamed under vacuum to obtain a collagen suspension.

[0057] In some preferred embodiments, 5-30 parts of gel-like collagen solution and 70-95 parts of collagen fiber solution are taken, and the two are stirred evenly and defoamed under vacuum to obtain a collagen suspension.

[0058] In some preferred embodiments, the gel-like collagen solution is a viscoelastic gel system prepared by thoroughly pulverizing the decellularized matrix. The system is homogeneous and contains more physical entanglements. After freeze-drying, it achieves a relatively uniform pore structure. However, because it disrupts most of the natural connections between fibers, its mechanical strength is low and it is easily degraded. In contrast, the decellularized matrix particles used in the preparation of collagen fiber solution are larger, retaining more of the natural structure, resulting in high mechanical strength but a longer degradation time. However, collagen fiber solution is an unstable dispersion system. When collagen fiber solution is prepared into a freeze-dried sponge alone, the sponge structure is uneven and easily collapses after absorbing water due to the low inter-fiber bonding strength. Therefore, we mix the gel-like collagen solution and collagen fiber solution in a certain proportion, where the gel-like collagen solution also acts as a thickener or binder, so that the final sponge structure possesses mechanical properties, volume retention, and a uniform pore structure, making it less prone to collapse after absorbing liquid.

[0059] Furthermore, the collagen suspension is extruded into a mold for molding and freeze-dried to obtain a collagen freeze-dried sponge. This sponge is then subjected to physical cross-linking, specifically gradient thermal cross-linking. This involves placing the collagen freeze-dried sponge in a vacuum chamber, evacuating to less than -100 kPa, and maintaining the temperature at 25℃-30℃ for 1-2 hours; then gradient heating to 80℃-85℃ and holding for 2-3 hours; followed by further heating to 100℃-105℃ and holding for 2-3 hours; and finally heating to 120℃-125℃ and holding for 24-48 hours.

[0060] It should be noted that the collagen freeze-dried sponge has undergone physical cross-linking treatment, which increases the interaction between collagen fibers, making the volume maintenance of the collagen matrix biomembrane better, and ensuring good biocompatibility.

[0061] In this invention, the introduction of more physical entanglements and gradient thermal crosslinking significantly enhances the interaction strength between collagen fibers, fundamentally improving the volume retention and degradability of oral wound materials. In this invention, the collagen fibers in the collagen fiber solution undergo swelling and salting-out processes, resulting in shrinkage and a denser structure, thus better resisting swelling. Gradient thermal crosslinking is a physical crosslinking method where the carboxyl and amino groups of adjacent amino acid side chains undergo condensation reactions to form ester and amide bonds. This crosslinking method does not excessively disrupt the triple helix structure of collagen and does not introduce additional chemical crosslinking agents. Experiments revealed that the shrunken collagen fiber structure also means fewer active groups, resulting in low crosslinking density after gradient thermal crosslinking, which does not effectively improve the absorption and disintegration phenomenon. Therefore, we further introduce a gel-like collagen solution. This gel-like collagen solution contains more physically entangled structures, which, after thorough mixing with the collagen fibers, can act as bridges, increasing the interaction between collagen fibers and connecting them into a unified whole. After gradient thermal crosslinking, more ester bonds and amide bonds are formed, resulting in oral wound materials that do not show obvious collapse after liquid absorption and have excellent volume maintenance.

[0062] The present invention also provides an oral wound material prepared by the above method, comprising a gel-like collagen liquid freeze-dried layer and a collagen fiber liquid freeze-dried layer, wherein the oral wound material is a porous, sponge-like material, and may be either sheet-like or cylindrical.

[0063] In some preferred embodiments, the oral wound material is obtained by lyophilizing a mixture of gel-like collagen solution and collagen fiber solution, with the lyophilized gel-like collagen solution layer and the lyophilized collagen fiber solution layer interwoven. Physical cross-linking further enhances the volume retention and degradation performance of the oral wound material. During use, the oral wound material rapidly absorbs blood and adapts to the shape of the extraction socket, filling it completely, thereby stabilizing the blood clot and promoting tissue repair.

[0064] To further illustrate the present invention, the following describes in detail, with reference to embodiments, an oral wound material and its preparation method provided by the present invention.

[0065] All raw materials and reagents used in the following examples are commercially available.

[0066] Example 1

[0067] In this embodiment, the naturally derived tissue was selected from the submucosa of porcine small intestine. First, a decellularized matrix was prepared. Excess tissue was removed from the porcine small intestine, and the tissue was soaked in a 0.1% peracetic acid solution for 1 hour, followed by rinsing with running water. The intestine was then shaken and washed for 1 hour with a mixed solution of 0.05% trypsin and 0.05% sodium dodecyl sulfate, followed by rinsing with running water again. Finally, the tissue was degreased by soaking in 75% isopropanol, and freeze-dried to obtain the decellularized submucosa matrix of porcine small intestine. The above pretreatment, virus inactivation, degreasing, decellularization, and drying steps are conventional steps in the prior art, and their details are not further elaborated here.

[0068] Gel-like collagen solution and collagen fiber solution were prepared using the above-mentioned decellularized matrix of the submucosa of porcine small intestine.

[0069] To prepare a collagen-like solution, the decellularized matrix of the submucosa of the small intestine was shredded and suspended in pure water to make the mass percentage of the decellularized matrix 1.0%. The pH of the pure water was adjusted to 3.0 with acetic acid. The decellularized matrix was then pulverized into a gel-like state using a tissue homogenizer to obtain a gel-like collagen solution.

[0070] Collagen fiber solution was prepared by grinding the decellularized submucosa matrix of porcine small intestine into irregular particles with a particle size of 0.2 mm-2 mm using low-temperature grinding, and suspending it in pure water to make the mass percentage of decellularized matrix particles 3.0%. The pH of the pure water was adjusted to 3.0 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.5 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 3.0 to make the mass percentage of collagen fibers 3%, and mechanical stirring was used to make the collagen fibers exhibit a slightly swollen and uniformly dispersed state, resulting in collagen fiber solution.

[0071] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 20 parts gel-like collagen solution and 80 parts collagen fiber solution are mixed, stirred evenly and defoamed under vacuum to obtain collagen suspension.

[0072] Collagen suspension was extruded into a mold and shaped. After shaping, it was freeze-dried to obtain a collagen freeze-dried sponge. The collagen freeze-dried sponge was then placed in a vacuum chamber, evacuated to -110 kPa, and held at 25°C for 2 hours. Gradual temperature crosslinking was then performed: the temperature was increased to 80°C and held for 3 hours; the temperature was further increased to 100°C and held for 3 hours; the temperature was increased to 120°C and held for 48 hours. After cooling to room temperature, an oral wound material was obtained.

[0073] Example 2

[0074] In this embodiment, porcine pericardium was selected as the naturally sourced tissue. First, a decellularized matrix was prepared. Excess tissue was removed from the porcine pericardium tissue, and it was soaked in a 0.1% peracetic acid solution for 1 hour, followed by rinsing with running water. Then, it was shaken and washed for 1 hour with a mixed solution of 0.05% trypsin and 0.05% sodium dodecyl sulfate, and rinsed again with running water. Finally, it was degreased by soaking in 75% isopropanol and freeze-dried to obtain the decellularized porcine pericardium matrix. The above pretreatment, virus inactivation, degreasing, decellularization, and drying steps are conventional steps in the prior art, and their details are not further elaborated here.

[0075] Gel-like collagen solution and collagen fiber solution were prepared using the above-mentioned decellularized porcine pericardium matrix.

[0076] Preparation of collagen-like collagen solution: The decellularized matrix of porcine pericardium was cut into small pieces and suspended in pure water to make the mass percentage of the decellularized matrix 0.5%. The pH was adjusted to 4.0 with acetic acid. The decellularized matrix was then pulverized into a gel-like state using a tissue homogenizer to obtain a gel-like collagen solution.

[0077] Preparation of collagen fiber solution: Porcine pericardial decellularized matrix was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to achieve a mass percentage of 3.0% for the decellularized matrix particles. The pH of the pure water was adjusted to 3.0 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.5 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 4.0 to achieve a mass percentage of 6% for the collagen fibers. Mechanical stirring was used to achieve a slightly swollen and uniformly dispersed collagen fiber solution.

[0078] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 5 parts gel-like collagen solution and 95 parts collagen fiber solution are mixed, stirred evenly, and defoamed under vacuum to obtain collagen suspension.

[0079] Collagen suspension was extruded into a mold and shaped. After shaping, it was freeze-dried to obtain a collagen freeze-dried sponge. The collagen freeze-dried sponge was then placed in a vacuum chamber, evacuated to -110 kPa, and held at 30°C for 1 hour. Gradual temperature crosslinking was then performed: the temperature was increased to 85°C and held for 2 hours; the temperature was further increased to 105°C and held for 2 hours; and the temperature was increased to 125°C and held for 24 hours. After cooling to room temperature, an oral wound material was obtained.

[0080] Example 3

[0081] In this embodiment, decellularized submucosa matrix of porcine small intestine and decellularized pericardium matrix were prepared using the methods described in Examples 1 and 2.

[0082] A gel-like collagen solution was prepared using the above-mentioned decellularized submucosa matrix of porcine small intestine, and a collagen fiber solution was prepared using the above-mentioned decellularized pericardium matrix of porcine pericardium.

[0083] Preparation of gel-like collagen solution: The decellularized matrix of the submucosa of porcine small intestine was cut into small pieces and suspended in pure water to make the mass percentage of the decellularized matrix 2%. The pH was adjusted to 4.0 with acetic acid. The decellularized matrix was then pulverized into a gel state using a tissue homogenizer to obtain a gel-like collagen solution.

[0084] Preparation of collagen fiber solution: Porcine pericardial decellularized matrix was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to achieve a mass percentage of 2.0% for the decellularized matrix particles. The pH was adjusted to 2.5 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.0 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 4.0 to achieve a mass percentage of 4% for the collagen fibers. Mechanical stirring was used to achieve a slightly swollen and uniformly dispersed collagen fiber solution.

[0085] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 10 parts gel-like collagen solution and 90 parts collagen fiber solution are mixed, stirred evenly and defoamed under vacuum to obtain collagen suspension.

[0086] Collagen suspension was extruded into a mold and shaped. After shaping, it was freeze-dried to obtain a collagen freeze-dried sponge. The collagen freeze-dried sponge was then placed in a vacuum chamber, evacuated to less than -100 kPa, and held at 30°C for 1 hour. Gradual temperature crosslinking was then performed: the temperature was increased to 80°C and held for 2 hours; the temperature was further increased to 100°C and held for 2 hours; the temperature was increased to 120°C and held for 36 hours. After cooling to room temperature, an oral wound material was obtained.

[0087] Example 4

[0088] In this embodiment, decellularized submucosa matrix of porcine small intestine and decellularized pericardium matrix were prepared using the methods described in Examples 1 and 2.

[0089] A gel-like collagen solution was prepared using the above-mentioned decellularized porcine pericardium matrix, and a collagen fiber solution was prepared using the above-mentioned decellularized porcine small intestinal submucosa matrix.

[0090] Preparation of gel-like collagen solution: The decellularized matrix of porcine pericardium was cut into small pieces and suspended in pure water to make the mass percentage of the decellularized matrix 3.0%. The pH was adjusted to 3.0 with acetic acid. The decellularized matrix was then pulverized into a gel state using a tissue homogenizer to obtain a gel-like collagen solution.

[0091] Preparation of collagen fiber solution: The decellularized submucosa matrix of porcine small intestine was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to achieve a mass percentage of 0.5% for the decellularized matrix particles. The pH was adjusted to 2.5 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.0 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 3.0 to achieve a mass percentage of 1% for the collagen fibers. Mechanical stirring was used to achieve a slightly swollen and uniformly dispersed collagen fiber solution.

[0092] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 30 parts gel-like collagen solution and 70 parts collagen fiber solution are mixed, stirred evenly and defoamed under vacuum to obtain collagen suspension.

[0093] Collagen suspension was extruded into a mold and shaped. After shaping, it was freeze-dried to obtain a collagen freeze-dried sponge. The collagen freeze-dried sponge was then placed in a vacuum chamber, evacuated to -110 kPa, and held at 25°C for 2 hours. Gradual temperature crosslinking was then performed: the temperature was increased to 80°C and held for 3 hours; the temperature was further increased to 100°C and held for 3 hours; the temperature was increased to 120°C and held for 48 hours. After cooling to room temperature, an oral wound material was obtained.

[0094] Comparative Example 1

[0095] In this embodiment, the method described in Example 1 was used to prepare a layered decellularized matrix of the porcine small intestinal submucosa. Compared with Example 1, the collagen suspension in Comparative Example 1 was replaced with collagen fiber solution.

[0096] Collagen fiber solution was prepared by grinding the decellularized submucosa matrix of porcine small intestine into irregular particles with a particle size of 0.2 mm-2 mm using low-temperature grinding, and suspending it in pure water to make the mass percentage of decellularized matrix particles 3.0%. The pH of the pure water was adjusted to 3.0 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.5 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 3.0 to make the mass percentage of collagen fibers 3%, and mechanical stirring was used to make the collagen fibers exhibit a slightly swollen and uniformly dispersed state, resulting in collagen fiber solution.

[0097] Collagen fiber liquid was extruded and injected into a mold to form a gel. After molding, it was freeze-dried to obtain a collagen freeze-dried sponge. The collagen freeze-dried sponge was then placed in a vacuum chamber, evacuated to -110 kPa, and held at 25°C for 2 hours. Gradual temperature crosslinking was then performed: the temperature was increased to 80°C and held for 3 hours; the temperature was further increased to 100°C and held for 3 hours; the temperature was increased to 120°C and held for 48 hours. After cooling to room temperature, an oral wound material was obtained.

[0098] Comparative Example 2

[0099] In this embodiment, the method described in Example 1 was used to prepare a layered decellularized submucosal matrix of porcine small intestine. Compared with Example 1, the oral wound material in Comparative Example 2 was not cross-linked.

[0100] Preparation of gel-like collagen solution: The decellularized matrix of the submucosa of pig small intestine was cut into small pieces and suspended in pure water to make the mass percentage of the decellularized matrix 1.0%. The pH value of the pure water was adjusted to 3.0 with acetic acid. The decellularized matrix was then pulverized into a gel state using a tissue homogenizer to obtain gel-like collagen solution.

[0101] Preparation of collagen fiber solution: The decellularized submucosa matrix of porcine small intestine was pulverized into irregular particles with a particle size of 0.2 mm-2 mm by low-temperature grinding and suspended in pure water to achieve a mass percentage of 3.0% for the decellularized matrix particles. The pH was adjusted to 3.0 with acetic acid to allow the decellularized matrix particles to fully swell, resulting in a decellularized matrix suspension. Sodium chloride powder was added to the decellularized matrix suspension until the sodium chloride concentration reached 2.5 mol / L, resulting in a white salting-out precipitate. The white salting-out precipitate was washed with PBS buffer and centrifuged to obtain concentrated collagen fibers. The collagen fibers were placed in acetic acid at pH 3.0 to achieve a mass percentage of 3% for the collagen fibers. Mechanical stirring was used to achieve a slightly swollen and uniformly dispersed collagen fiber solution.

[0102] Collagen suspension is prepared from gel-like collagen solution and collagen fiber solution. 20 parts gel-like collagen solution and 80 parts collagen fiber solution are mixed, stirred evenly and defoamed under vacuum to obtain collagen suspension.

[0103] Collagen suspension is extruded into a mold to form a shape. After forming, it is freeze-dried to obtain an oral wound material that has not undergone cross-linking treatment.

[0104] Comparative Test

[0105] ① Cytotoxicity test: The oral wound materials prepared in Example 1 and Comparative Examples 1 and 2 were tested using the MTT assay according to the national standard GB / T16886.5-2017 "Biological evaluation of medical devices - Part 5: In vitro cytotoxicity test". L929 mouse fibroblasts were used. Each group of test samples was added to serum-containing culture medium and extracted at 37°C for 24 hours. The extract was then added to the cells and cultured for 24 hours. The cytotoxicity was detected by the MTT assay (n=3). The test results are shown in Table 1:

[0106] Table 1. Cytotoxicity test results of oral wound materials prepared in Example 1 and Comparative Examples 1 and 2

[0107] Example 1 93.53 Comparative Example 1 92.15 Comparative Example 2 90.23

[0108] Table 1 shows that the cell viability rates of Sample 1, Comparative Examples 1 and 2 were 93.60%, 94.47%, and 95.63%, respectively. The cell viability results in Sample 1 and Comparative Example 1 were similar, while the cell viability rate in Comparative Example 2 was slightly higher due to the absence of cross-linking treatment. Because the proportion of denatured collagen fibers during gradient thermal cross-linking is very small, the oral wound material after gradient thermal cross-linking still exhibits very low cytotoxicity.

[0109] ② In vitro degradation test: The oral wound materials obtained in Example 1, Comparative Examples 1 and 2 were weighed and recorded as W0. Under aseptic conditions at 37°C, the samples were immersed in PBS buffer solution containing 20 U / mL collagenase and allowed to stand. Samples were taken at 6h, 8h, and 12h, vacuum dried, and weighed, recorded as W1. The degradation rate was calculated using the following formula, and the degradation calculation results are shown in Table 2:

[0110]

[0111] Table 2. In vitro degradation test results of oral wound materials prepared in Example 1 and Comparative Examples 1 and 2

[0112] Example 1 54.65% 78.97% 100% Comparative Example 1 55.17% 73.12% 100% Comparative Example 2 72.45% 95.37% 100%

[0113] The results showed that Example 1 and Comparative Example 1 had similar in vitro degradation processes, while Comparative Example 2 degraded faster because it did not undergo cross-linking treatment.

[0114] ③ Tensile strength test: The oral wound material was cut into strips with a width of 10 mm. The two ends of the product were clamped with fixtures, and the tensile testing machine was turned on at a speed of 100 mm / min to test the tensile strength (MPa). The results are shown in Table 3:

[0115] Table 3. Tensile strength test results of oral wound materials prepared in Example 1 and Comparative Examples 1 and 2

[0116] Tensile strength of sponge layer 13.75 8.58 7.36

[0117] The results showed that the oral wound material in Example 1 had the highest tensile strength, followed by the oral wound material in Comparative Example 1, while the tensile strength of the material in Comparative Example 2 was the lowest. The collagen suspension in Comparative Example 1 used only collagen fiber liquid without adding gel-like collagen liquid, resulting in a lack of entanglement between the collagen fibers in the sponge, leading to a significantly lower tensile strength compared to Example 1. The oral wound material in Comparative Example 2, lacking cross-linking treatment, also exhibited lower tensile strength. These results indicate that oral wound materials incorporating gel-like collagen liquid and undergoing gradient thermal cross-linking treatment possess better mechanical strength.

[0118] ④ Qualitative test of water absorption and volume stability: Select an imported product H, a self-made oral wound material M, and a domestic product P for a comparative experiment on water absorption and volume stability. Squeeze samples H, M, and P flat by hand and observe their resilience after releasing the pressure; place the flattened samples H, M, and P in excess water and observe their water absorption and volume stability.

[0119] The results showed that, Figure 2 As shown, a is the original state of the sample, b is the state of the sample after being flattened, and c is the state of the sample after absorbing water. In any of the three samples in any figure, from left to right, they are imported product H, self-made oral wound material M, and domestic product P.

[0120] like Figure 2 b. Squeeze samples H, M, and P firmly with your hands. After releasing your hands, samples H and M show some resilience, while sample P shows no obvious resilience. Figure 2 c. When samples H, M, and P were placed in excess water, sample H absorbed water slowly and could not return to its original volume after absorbing water, showing significant volume shrinkage. In contrast, M and P absorbed water rapidly; sample M returned to its original volume after absorbing water, while sample P could not return to its original volume after absorbing water, showing significant volume shrinkage. These results indicate that, compared to an imported product H and a domestically produced product P, the self-made oral wound material has better water absorption and...

[0121] The specific embodiments of this application have been described in detail above. For those skilled in the art, several improvements and modifications can be made to this application without departing from the principle of this application, and these improvements and modifications also fall within the protection scope of the claims of this application.

Claims

1. A method for preparing oral wound material, characterized in that, Includes the following steps: S1: Prepare gel-like collagen solution; S2: Preparation of collagen fiber solution; S3: Mix 5-30 parts of gel-like collagen solution and 70-95 parts of collagen fiber solution, stir evenly and remove bubbles under vacuum to obtain collagen suspension; S4: The collagen suspension is squeezed into a mold to form a shape and then freeze-dried to obtain a collagen freeze-dried sponge; S5: Gradient thermal cross-linking of collagen freeze-dried sponge to obtain oral wound material; The preparation step of the gel-like collagen solution in step S1 includes: S101 Decellularization: A decellularized matrix is ​​prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin; S102 pulverization: After the decellularized matrix is ​​pulverized, it is suspended in pure water, wherein the mass percentage of the decellularized matrix is ​​0.5%-3.0%. Then, the pH value is adjusted to 3.0-4.0 with acid, and the decellularized matrix is ​​pulverized into a gel state using a tissue homogenizer to obtain a gel-like collagen solution. The preparation step of the collagen fiber solution in step S2 includes: S201 Decellularization: A decellularized matrix is ​​prepared by pretreatment, virus inactivation, defatting, decellularization, and drying of animal tissues of natural origin; S202 pulverization: The decellularized matrix is ​​pulverized into irregular particles with a particle size of 0.2mm-2mm by low-temperature grinding and suspended in pure water. The mass percentage of the decellularized matrix particles is 0.5%-3.0%. The pH value is adjusted to 2.5-3.0 with acid to fully swell the decellularized matrix particles and obtain a decellularized matrix suspension. S203 dehydration: Add sodium chloride powder to the decellularized matrix suspension until the sodium chloride concentration reaches 2.0-2.5 mol / L to obtain a white salting-out precipitate. Wash the white salting-out precipitate with PBS buffer and centrifuge to obtain concentrated collagen fibers. S204 dispersion: Collagen fibers are placed in an acid with a pH of 3.0-4.0, so that the mass percentage of collagen fibers is 1%-6%. The collagen fibers are mechanically stirred until they exhibit a slightly swollen and uniformly dispersed state, thus obtaining a collagen fiber solution.

2. The method for preparing oral wound material according to claim 1, characterized in that: The acids include hydrochloric acid, acetic acid, and citric acid.

3. The method for preparing oral wound material according to claim 1, characterized in that: The naturally derived animal tissues include the submucosa of the small intestine of pigs or cattle, the peritoneum of pigs or cattle, the pericardium of pigs or cattle, the dermis of pigs or cattle, and the bladder of pigs or cattle.

4. The method for preparing oral wound material according to claim 1, characterized in that: The gradient thermal crosslinking in step S5 involves placing the collagen layer in a vacuum chamber, evacuating it to less than -100 kPa, and maintaining it at 25℃-30℃ for 1-2 hours; then performing gradient temperature crosslinking by raising the temperature to 80℃-85℃ and holding it for 2-3 hours; continuing to raise the temperature to 100℃-105℃ and holding it for 2-3 hours; and finally raising the temperature to 120℃-125℃ and holding it for 24-48 hours.

5. An oral wound material, characterized in that: The oral wound material is prepared by any one of the methods described in claims 1 to 4, comprising a gel-like collagen liquid freeze-dried layer and a collagen fiber liquid freeze-dried layer interwoven with each other.

Citation Information

Patent Citations

  • A kind of acellular matrix wound material and preparation method thereof

    CN115845116B

  • Material for promoting operation wound heal and preparation method thereof

    CN101507831A

  • Acellular matrix composite material for chronic wounds

    CN117298322A